Optimalisasi Media Podcast dalam Pembelajaran Jarak Jauh untuk Ekstrakurikuler Kelompok Ilmiah Remaja di SMA Negeri 1 Tambangan Kabupaten Mandailing Natal - Ali, Muttaqin Kholis; Ali, Al Muhtadibillah; Hasanah, Arrahmil (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to optimize the use of podcast media in distance learning for extracurricular Youth Scientific Groups (KIR) at SMA Negeri 1 Tambangan, Mandailing Natal Regency. This research uses the Research and Development (R&D) method with the ADDIE model. The subject of this study involved 35 KIR member students. Podcast development goes through the stages of analysis, design, development, implementation, and evaluation. The results showed that the developed podcast received a